White-Collar Workers and Neighbourhood Change: Jarvis Street in Toronto, 1880–1920 - Lombardo, Nicholas (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2014)
In 1880, Jarvis Street, just east of Toronto’s central business district, was the city’s premier residential district, home to notable Torontonians such as the Masseys and the Gooderhams. By 1920, the street would host a new group of young, unattached, white-collar workers. Changes to the social, demographic, and occupational character of Jarvis Street were accompanied by physical changes to its built form. The family estates of the nineteenth-century elite were converted into boarding and rooming houses, or torn down and replaced by some of the city’s first apartment buildings. These changes were driven by the growth of corporate capitalism in Toronto and the attendant growth of white-collar workers, as well as changes to urban form associated with the growth of the city outwards. This article examines the relationship between neighbourhood change and larger socio-economic changes occurring across the North American urban landscape at the time. It does so by using a variety of historical data, including City of Toronto tax assessments, city directories, as well as contemporary newspaper accounts. This case study of Jarvis Street’s social, gender, occupational, and physical changes shows the way that larger socio-economic processes are written at the scale of the neighbourhood. In doing so, it demonstrates the importance of understanding neighbourhood change as local materialization of larger social, economic, and demographic processes.